The Speed and Torque Control of Direct Current Servo Motors by using Cascade Fuzzy PI Controller - (:unkn) unknown (WYDAWNICTWO SIGMA-N O T SP Z O O, 2012)
Direct current servo motors (DCSMs) are frequently used in the areas of industry which require different operating conditions. Traditional PI controllers with constant coefficients are not sufficient for the speed and torque control of these motors, because of that their dynamic characteristics change in different operating conditions. The speed and load changes cause positive and negative overshoots and oscillations. In this study, in order to overcome these problems, the speed and torque controls of DCSM were implemented by using the cascade fuzzy PI controller, where the torque control was carried out by the current control. For this aim, a cascade fuzzy PI controller was designed for controlling the speed and the current of DCSM. Here, the fuzzy logic controllers in cascade fuzzy PI controllers adjusted the proportional and integral coefficients according to the speed and the change of speed, and the current and the change of current. The experimental results showed that the performance of cascade fuzzy PI controller was better than that of traditional PI controller for different operating speed and load conditions.
Keywords: Direct current servo motor; PI controller; Cascade fuzzy PI controller; STATE